Efeito do extrato etanólico de Caesalpinia pyramidalis tul. na pancreatite aguda em ratos - Santana, Danielle Gomes (2011)
Acute pancreatitis (AP) is a pancreatic inflammatory disease that usually occurs associated with abdominal pain and presents high mortality in its severe form. There is no specific therapy to treat this disease, as well as the secondary lung injury, which makes of interest the search for new substances to treat AP. In this context, the use of medicinal plants can be a reasonable strategy to treat this inflammatory condition and the associated pain. We investigated therefore the effect of ethanol extract of the inner bark of Caesalpinia pyramidalis Tul. (Fabaceae) (EECp) on AP induced by common bile duct obstruction (CBDO). Firstly, chromatographic analysis of the EECp was performed by high performance liquid chromatography (HPLC) technique. Groups of male Wistar rats (200-250 g, n = 6-8 per group) were submitted to CBDO and euthanized 6 (protocol 1) or 24 h (protocol 2) thereafter. Animals were orally treated with EECp (100, 200 or 400 mg/kg, protocol 1, or 400 mg/kg, protocol 2) or vehicle (Tween 80, 0.2% in saline 0.9%) 1 h before and 12 h after induction of AP or false surgery (sham). Before (-1 h) and after 6, 12 or 24 h, the abdominal hyperalgesia was measured using the electronic von Frey. The locomotor activity of the animals was evaluated by the open field test. After euthanasia and tissue collection the following parameters were measured: (i) the activity of myeloperoxidase (MPO) in pancreas and lung, (ii) the concentration of malondialdehyde (MDA) in pancreas, lung, liver, and kidney, (iii) the pancreatic edema index, (iv) serum amylase, lipase, and nitrate/nitrite and (v) the total and differential leukocyte count in peripheral blood. The chromatographic analysis of EECp suggested that rutin is present in this extract. In both protocols 1 and 2 the CBDO significantly increased all inflammatory and biochemical parameters evaluated, when compared to sham group. The effects caused by EECp on CBDO-induced pancreatitis include the reduction of pancreatic inflammation, because of inhibition of neutrophil infiltration, and pancreatic edema, attenuation of systemic inflammation, by decreasing the leukocyte counts in peripheral blood, as well as reducing the pulmonary neutrophil infiltration, especially in the initial stages of pancreatitis. Also, the EECp decreased the pancreatic and lung lipid peroxidation and the serum nitrate/nitrite, which may contribute to the anti-inflammatory effects observed in these tissues and it partially reduced the amylase and lipase levels. Abdominal hyperalgesia induced by CBDO was completely inhibited by EECp (400 mg/kg), an effect that persists for at least 12 h. No alterations were observed in the locomotor activity of rats treated with EECp in the open field. The results showed that EECp decreases the inflammatory and nociceptive responses in CBDO-induced AP. These activities make this extract of interest to the development of studies or approaches for the treatment of this condition in humans.